Using of Special Knowledge for Investigations of Criminal Feigns in Economic Activity - DILBARHANOVA, Zhanat Rahimzhanovna; ABIZHANOV, Syrym Maratovich; DZHUMATOV, Aidynbek Baltabekovich; SANAPIYANOVA, Assel Nursainovna (Journal of Advanced Research in Law and Economics; Vol 7 No 1 (2016): JARLE Volume VII, Issue 1(15), Spring 2016, 2016)
This paper covers on criminal offences committed via feigns and concealments, studies the recommendations for creating methodologies for investigating crimes in economic activity related to criminal feigns and auxiliary methods to arrange feigns. The objective of this paper is to study, analyse and generalize court and investigative practice, to analyze the experience of criminology scholars, to develop general provisions for crime investigation focusing on economic crimes. Then, accounting for the contemporary reality of the crime situation where we see more and more sophisticated, concealed acts causing great damage to the public and country, we distinguished crimes in economic, financial and credit, financial and budget spheres.